Effectiveness of tobacco cessation interventions for different groups of tobacco users in Sweden: a study protocol for a national prospective cohort study. Issue 1 (25th January 2022) - Rasmussen, Mette; Larsson, Matz; Gilljam, Hans; Adami, Johanna; Wärjerstam, Sanne; Post, Ann; Björk-Eriksson, Thomas; Helgason, Asgeir R; Tønnesen, Hanne
Abstract : Introduction: Tobacco is still one of the single most important risk factors among the lifestyle habits that cause morbidity and mortality in humans. Furthermore, tobacco has a heavy social gradient, as the consequences are even worse among disadvantaged and vulnerable groups. To reduce tobacco-related inequity in health, those most in need should be offered the most effective tobacco cessation intervention. The aim of this study is to facilitate and improve the evaluation of already implemented national tobacco cessation efforts, focusing on 10 disadvantaged and vulnerable groups of tobacco users. Methods and analysis: This is a prospective cohort study. Data will be collected by established tobacco cessation counsellors in Sweden. The study includes adult tobacco or e-cigarette users, including disadvantaged and vulnerable patients, receiving in-person interventions for tobacco or e-cigarette cessation (smoking, snus and/or e-cigarettes). Patient inclusion was initiated in April 2020. For data analyses patients will be sorted into vulnerable groups based on risk factors and compared with tobacco users without the risk factor in question. The primary outcome is continuous successful quitting after 6 months, measured by self-reporting. Secondary outcomes include abstinence at the end of the treatment programme, which could be from minutes over days to weeks, 14-day point prevalence after 6 months, and patient satisfaction with the intervention. Effectiveness of successful quitting will be examined by comparing vulnerable with non-vulnerable patients using a mixed-effect logistic regression model adjusting for potential prognostic factors and known confounders. Ethics and dissemination: The project will follow the guidelines from the Swedish Data Protection Authority and have been approved by the Swedish Ethical Review Authority before patient inclusion (Dnr: 2019-02221). Only patients providing written informed consent will be included. Both positive and negative results will be published in scientific peer-reviewed journals and presented at national and international conferences. Information will be provided through media available to the public, politicians, healthcare providers and planners as these are all important stakeholders. Trial registration number: NCT04819152 .